2012
DOI: 10.1073/pnas.1205176109
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and sequence-independent replication of DNA containing a third base pair establishes a functional six-letter genetic alphabet

Abstract: The natural four-letter genetic alphabet, comprised of just two base pairs (dA-dT and dG-dC), is conserved throughout all life, and its expansion by the development of a third, unnatural base pair has emerged as a central goal of chemical and synthetic biology. We recently developed a class of candidate unnatural base pairs, exemplified by the pair formed between d5SICS and dNaM. Here, we examine the PCR amplification of DNA containing one or more d5SICS-dNaM pairs in a wide variety of sequence contexts. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
131
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 159 publications
(134 citation statements)
references
References 43 publications
2
131
0
1
Order By: Relevance
“…1A) being a particularly promising example (5)(6)(7). Despite lacking complementary hydrogen bonding, we demonstrated that the dNaM-d5SICS UBP is well replicated by a variety of DNA polymerases in vitro (7)(8)(9)(10), and that this efficient replication is mediated by a unique mechanism that draws upon interbase hydrophobic and packing interactions (11,12). These efforts then culminated in the first progress toward the creation of an SSO in 2014, when we reported that Escherichia coli grown in the presence of the corresponding unnatural nucleoside triphosphates (dNaMTP and d5SICSTP), and provided with a plasmid-encoded nucleoside triphosphate transporter (NTT2) from Phaeodactylum tricornutum (which we denote as PtNTT2) (13), is able to import the unnatural triphosphates and replicate a single dNaM-d5SICS UBP on a second plasmid (14).…”
mentioning
confidence: 82%
“…1A) being a particularly promising example (5)(6)(7). Despite lacking complementary hydrogen bonding, we demonstrated that the dNaM-d5SICS UBP is well replicated by a variety of DNA polymerases in vitro (7)(8)(9)(10), and that this efficient replication is mediated by a unique mechanism that draws upon interbase hydrophobic and packing interactions (11,12). These efforts then culminated in the first progress toward the creation of an SSO in 2014, when we reported that Escherichia coli grown in the presence of the corresponding unnatural nucleoside triphosphates (dNaMTP and d5SICSTP), and provided with a plasmid-encoded nucleoside triphosphate transporter (NTT2) from Phaeodactylum tricornutum (which we denote as PtNTT2) (13), is able to import the unnatural triphosphates and replicate a single dNaM-d5SICS UBP on a second plasmid (14).…”
mentioning
confidence: 82%
“…This form of targeted sequencing is more appropriate for applications such as microbiomic experiments where community composition is analyzed by surveying 16S rRNA sequences in complex bacterial mixtures (57), analysis of antibody diversity (58) and T cell receptor gene repertoires (50), and facilitating the process of identifying and selecting high value aptamers in a SELEX protocol (59). To highlight the flexibility of amplicon sequencing, a recent study used the method to analyze the incorporation of unnatural nucleotides during DNA synthesis (60). …”
Section: Sample Preparation For Ngs Applications: Targeted and Amplicmentioning
confidence: 99%
“…In fact, d NaM -d 5SICS was the first of our UBP candidates to be amplified in a standard PCR reaction with high efficiency and fidelity. 32 To determine whether d NaM is optimal for pairing with d 5SICS , we further explored derivatization of the d MMO2 scaffold with Cl, Br, I, Me, and Pr meta-substituents, but none improved replication. 33 We next examined 28 analogs with different para-substituents, and the SAR was augmented with PCR amplification assays using Taq, OneTaq, and KOD polymerases (Figure 9A).…”
Section: Parts Optimization: Third Generation Ubp Candidatesmentioning
confidence: 99%